Economic labour exploitation, companies and criminal organizations: a critical review in criminal law in Spain. - Gil Nobajas, María Soledad (2021)
This paper analyzes the response offered by the Spanish Criminal Code to business crime in cases of productive or economic labor exploitation. For this purpose, these forms of more serious criminal exploitation are systematized, to address the specific legal-criminal treatment that corresponds to the various situations in which legal persons and criminal organizations are involved, as well as the adequacy of the criminal response to these cases.